Status and development in the dairy sector in the BRIC - Mikhail Ramanovich; Asaah Ndambi; Torsten Hemme (Leibniz Institute of Agricultural Development in Central and Eastern Europe (IAMO), 2011)
Milk production is a very important element of the whole dairy chain. The BRIC countries are among the top 6 milk producing countries and produce nearly one third of the world's total milk volume. A large number of dairy animals and a relatively low milk output per animal show a great potential of the BRIC for a further growth of production. In the same time the BRIC countries comprise 42% of world's population. Expected population and prosperity growth will lead to a further growth in milk demand. The BRIC countries have a competitive level of milk production cost in international comparison. The success of the BRIC counties in the international milk market will depend on the contribution of all stakeholders in the dairy chain: farmers, processors, supporting industries and policy makers.
Keywords: 330; Dairy sector; BRIC; Brazil; Russia; India; China; IFCN